Improvement of Cr-Co-Mo membrane surface used as barrier for bone regeneration through UV photofunctionalization: An in vitro study - Decco, Oscar Alfredo (2017)
Although there are several studies of the ultraviolet (UV) light-mediated photofunctionalization of titanium for use as implant material, the underlying mechanism is not fully understood. However, the results of in vitro and in vivo studies are very encouraging. The use of UV photofunctionalization as a surface treatment on other implant materials, as the Cr-Co-Mo alloy, has not been explored in depth. Using sandblasted Cr-Co-Mo discs, the surface photofunctionalization was studied for ultraviolet A (UVA, 365 nm) and ultraviolet C (UVC, 254 nm), and the surfaces were evaluated for their ability to sustain hydroxyapatite crystal growth through incubation in simulated body fluid for a seven-day period. The variation of the pre- and post-irradiation contact angle and surface composition was determined through the quantification of the weight percentage of Ca and P crystals by the EDAX ZAF method (EDS). Statistically significant differences (p < 0.05) were found for samples irradiated with UVA over 48 h, corresponding with hydrophilic surfaces, and the same result was found for samples exposed to 3 h of UVC. Superhydrophilic surfaces were found in samples irradiated for 12, 24 and 48 h with UVC. The decrease in the carbon content is related with the increase in the surface content of Ca and P, and vice versa over the Cr-Co-Mo surfaces.